Effects of Abrasive Waterjet Machining on the Quality of the Surface Generated on a Carbon Fibre Reinforced Polymer Composite - Andrew Rowe; Alokesh Pramanik; Animesh Kumar Basak; Chander Prakash; Shankar Subramaniam; Amit Rai Dixit; N. Radhika (Machines, 2023)
The effect of the water pressure, traverse speed, and abrasive feed rate on the circularity, cylindricity, kerf taper, and surface roughness of holes produced by abrasive waterjet machining (AWJM) of a carbon-fibre-reinforced polymer (CFRP) composite was investigated in the current study. It was found that the circularity deviation decreased as the water pressure was increased. Cylindricity was affected by all three parameters, although the abrasive feed rate caused the largest deviations as it increased. The surface roughness was affected by all three, but a clear connection was not able to be concluded. The kerf taper ratio reduced with an increase in water pressure, while it increased with an increase in the abrasive feed rate and an increase in the traverse speed. To obtain optimum results, the water pressure should be increased, the traverse speed should be decreased, and the abrasive feed rate can remain constant but is recommended to be slightly reduced.